Memory for non-painful auditory items is influenced by whether they are experienced in a context involving painful electrical stimulation - Vogt, Keith M. (Exp Brain Res, 2019)
In this study, we sought to examine the effect of experimentally-induced somatic pain on memory. Subjects heard a series of words and made categorization decisions in two different conditions. One condition included painful shocks administered just after presentation of some of the words; the other condition involved no shocks. For the condition that included painful stimulations, every other word was followed by a shock, and subjects were informed to expect this pattern. Word lists were repeated three times within each condition in randomized order, with different category judgments but consistent pain-word pairings. After a brief delay, recognition memory was assessed. Non-pain words from the pain condition were less strongly encoded than non-pain words from the completely pain-free condition. Recognition of pain-paired words was not significantly different than either subgroup of non-pain words. An important accompanying finding is that response times to repeated experimental items were slower for non-pain words from the pain condition, compared to non-pain words from the completely pain-free condition. This demonstrates that the effect of pain on memory may generalize to non-pain items experienced in the same experimental context.